Sauerkraut juice fermented with different symbiotic starter cultures: comprehensive assessment of physicochemical, rheological, antioxidant, and microbiological characteristics - Salek, Richardos Nikolaos; Pleva, Pavel; Sumczynski, Daniela; Vinter, Štěpán; Kopečková, Jana; Rejdlová, Anita; Lorencová, Eva (Frontiers in Sustainable Food Systems, 2025)
The current study investigated the fermentation of sauerkraut juice (SKJ) utilizing various symbiotic starter cultures (specifically kombucha and water kefir starter cultures, respectively). It aimed to assess the physicochemical, rheological, antioxidant, and microbiological properties of the resulting beverages. Black tea kombucha and apple juice water kefir fermented beverages were also analyzed for comparative purposes. Key parameters such as pH values, total acidity, total soluble solids, and total dissolved solids were measured. The initial pH exhibited significant variation, decreasing over the course of fermentation due to organic acid production. As fermentation progressed, total acidity increased, a phenomenon attributed to the activities of acetic and lactic acid bacteria. The flow behavior of the fermented beverages was characterized using the Power-law model, revealing that most samples displayed non-Newtonian behavior, indicating that their viscosity and shear stress changed with shear rate. Specifically, the consistency index declined while the flow behavior index rose. Additionally, seven biogenic amines were detected in the fermented samples, with their low concentrations posing minimal risk to consumer safety, resulting from microbial activity during fermentation. Antioxidant activity was assessed using DPPH and ABTS radical scavenging assays, revealing that black tea kombucha showed the highest levels of antioxidant activity. The total phenolic content varied between samples and decreased over time, particularly in the water kefir-like beverages. The microbiological analysis indicated a gradual increase in beneficial microorganisms, such as lactic acid bacteria and yeasts, throughout the fermentation process. These findings underscore the potential of SKJ as a promising base for developing functional beverages, providing valuable insights into how different fermentation starter cultures influence the quality and health-promoting properties of fermented beverages. In light of the growing consumer interest in functional, particularly plant-based foods, the fermentation of SKJ presents an opportunity to create probiotic-rich beverages.